Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense—15. The genus Opisthencentrus W. Horn (Coleoptera: Cicindelidae) - Moravec, Jiří (Zootaxa, 2016)
The Neotropical, monobasic tiger beetle genus Opisthencentrus W. Horn, 1893, based on Oxygonia dentipennis Germar, 1843, is presented along with a lectotype designation. Most of the diagnostic characters of Opisthencentrus dentipennis (Germar, 1843), including the aedeagus and structures of the internal sac, are illustrated for the first time. Redescription and illustrations in colour photographs of the habitus and diagnostic characters of the female lectotype (MFNB) and five other specimens of both sexes are provided. The validity of Opisthencentrus as a separate genus is confirmed and it is concluded that the genus is a natural member of the subtribe Odontocheilina W. Horn, 1899, markedly differing from the genus Oxygonia Mannerheim, 1837. The history of the taxonomy and relationship to other genera of the subtribe, as well as the biology and distribution of this very rare and hitherto little known tiger beetle in the Brazilian Atlantic rain-forest, are discussed.